Antimicrobial resistance control activities at a tertiary hospital in a low-resource setting: an example of Queen Elizabeth Central Hospital in Malawi - Kamalo, Patrick; Iroh Tam, Pui-Ying; Noniwa, Thokozani; Mpanga, Chikumbutso; Mulambia, Chanizya; Phiri, Ethwako; Kumwenda, Dingase; Phillipo, Ed; Lissauer, Samantha; Kulapani, David; Mwinjiwa, Christina (Frontiers in Antibiotics, 2023)
Background Addressing AMR has been most problematic in low- and middle-income countries, which lack infrastructure, diagnostic capacity, and robust data management systems, among other factors. The implementation of locally-led efforts in a low-income country to develop sustainability and build capacity for AMR control within the existing infrastructure has not been well documented. Methods We detail current AMR control initiatives at Queen Elizabeth Central Hospital, a tertiary referral government hospital in Malawi with limited resources, and present the activities accomplished to date, lessons learned, and challenges ahead. Results The key areas of AMR control initiatives that the group focused on included laboratory diagnostics and surveillance, antimicrobial stewardship, infection prevention and control, pharmacy, leadership, education, and funding. Discussion The hospital AMR Control Working Group increased awareness, built capacity, and implemented activities around AMR control throughout the hospital, in spite of the resource limitations in this setting. Our results are based on the substantial leadership provided by the working group and committed stakeholders who have taken ownership of this process. Conclusion Limited resources pose a challenge to the implementation of AMR control activities in low- and middle-income countries. Leadership is central to implementation. Future efforts will need to transition the initiative from an almost fully personal commitment to one with wider engagement to ensure sustainability.